Designing a 3D printed human derived artificial myo-structure for anal sphincter defects in anorectal malformations and adult secondary damage. (June 2018) - Testa, Stefano; Fuoco, Claudia; Costantini, Marco; Belli, Roberta; Fascetti Leon, Francesco; Vitiello, Libero; Rainer, Alberto; Cannata, Stefano; Gargioli, Cesare
Abstract: Fecal incontinence (FI) is a major social and economic burden. Adults suffering from post-surgery consequences or trauma and children affected by congenital anorectal malformations are the main categories of patients suffering from FI due to defective sphincter complex. Current therapeutic options for FI are often only partially effective, require lifelong care and are resource consuming. Besides, in both congenital and acquired anal sphincter defects, muscle damage is often irregular, leading to a diffuse derangement not suitable for surgical repair. In this context, regenerative medicine offers an increasing number of theoretically suitable solutions to restore sphincter structures, but only a few preclinical studies have been published regarding the use of cell therapy, biomaterials or tissue engineered structures for FI application. Here we present, for the first time, the generation of an in vitro engineered muscular sphincter using a population of adult human perivascular stem cells (pericytes) and 3D bioprinting. 3D bioprinting is an emerging technology for fabricating artificial tissue and organ constructs, which lends itself perfectly to the design of muscle constructs for anal sphincter repair. In our approach, 3D functional constructs have been created by simultaneously depositing cells and supporting material in a spatially defined, layer-by-layer stacking organization, generating a biomimetic spatial arrangement. Specifically, we developed a 3D myo-structure starting from human muscle derived pericytes, perivascular stem cells able to undergo robust myogenesis while also guaranteeing a rapid vascularization supporting and recruiting new blood vessels. The results presented here represent a pre-clinic study that strongly supports the feasibility of this innovative approach to treat the forms of fecal incontinence that are unresponsive to conservative treatments.